Perbandingan Penilaian Penyelenggaraan Pelayanan Publik Tahun 2021 dengan Tahun 2022 - Tiana Putra, Daru; Dewantoro, Faris; Arkaan Radianto Putra, Muhammad (PUBLICNESS: Journal of Public Administration Studies, 2023)
This research is used to see a comparison of the assessment of public service delivery in 2021 with 2022. This research uses descriptive qualitative research methods to explain the developed public service delivery assessment. An ombudsman institution in Indonesia assesses public service delivery called the Ombudsman RI. The results of this study found that there was indeed a comparison of the assessment of public service delivery in 2021 with 2022. First, the results of public services in 2022 will result in a Public Service Supervision Opinion, while 2021 only divides it into compliance zones. Second, the assessment method in 2022 will be more varied, ranging from interviews, data collection, and documentary evidence supporting services to observation. Interviews will be divided into service officer interviews and community interviews. If in 2021, only physical observation. Third, the locus of assessment of public service delivery in 2022 is broader than in 2021. Fourth, institutional assessments are divided into two categories: non-vertical and vertical institutions.